Accumulation of capsaicin in two chili pepper varieties (Capsicum annuum L.) at different stages of fruit maturity - Emese EGYED; Roxana L. STOIAN-DOD; Alexandru-Ioan APAHIDEAN; Emese GÁL; Sandor RÓZSA; Tincuța M. GOCAN; Dănuț-Nicolae MĂNIUȚIU (Notulae Botanicae Horti Agrobotanici Cluj-Napoca)
Chili peppers are appreciated and consumed especially for their sensorial attributes, but also because of their rich content in bioactive compounds. Capsaicin is one of the most important compounds found in peppers that gives them their spicy heat profile. Therefore, the main aim of this study was to determine the optimal harvesting time of hot peppers with the highest content in capsaicin. The capsaicin content of chili peppers depends on several factors, including the variety of pepper, growing conditions, and cultivation method. Capsaicin is mainly concentrated in the internal membranes of the pepper, where the seeds are also found. These biochemicals are used mostly in food industry, but anti-cancer effects have also been reported. To determine the capsaicin content, gas chromatographic analysis of volatile compounds was performed in both young and adult plants. ‘Hyffae F1’ and ‘Paprika giallo’ hot pepper hybrids grown in greenhouse conditions weew subjected to both chemical and organic cultivation treatments and two planting densities. The results obtained, showed that the capsaicin content varied between 12.11 and 39.01%. The highest quantity was recorded in ‘Paprika giallo’ under the influence of chemical treatments with the fruits were harvested at physiological maturity. The results also revealed that variations in capsaicin contents were rather influenced by harvesting time than the cultivar.